ANDROID-BASED EDUCATIONAL GAME INTRODUCING NOCTURAL AND DIURNAL ANIMALS - Mashuda, Putra Aisyifa; Rusdiana, Lili; Suparno (Yayasan Nuraini Ibrahim Mandiri, 2024)
Indonesian which The development of information technology in the form of education has begun to penetrate the world of entertainment. The combination of education and entertainment, makes this form of education not boring for its users. One of them is the existence of a game application to introduce nocturnal and diurnal animals. This game can spark the interest and enthusiasm of its users to study animals as one of the materials in science subjects. Applications with features as multimedia-based interactive learning media to help children learn in a more fun way. App features 6 nocturnal animals and 6 diurnal animals respectively. The application is also accompanied by a quiz feature in the form of multiple choice and displays the score on the quiz based on the correct number answered by the user.